Tidying-up the plant nuclear space: domains, functions, and dynamics - Santos, Ana Paula; Gaudin, Valérie; Mozgová, Iva; Pontvianne, Frédéric; Schubert, Daniel; Tek, Ahmet L; Dvořáčková, Martina; Liu, Chang; Fransz, Paul; Rosa, Stefanie; Farrona, Sara (Journal of experimental botany, 2020)
Understanding how the packaging of chromatin in the nucleus is regulated and organized to guide complex cellular and developmental programmes, as well as responses to environmental cues is a major question in biology. Technological advances have allowed remarkable progress within this field over the last years. However, we still know very little about how the 3D genome organization within the cell nucleus contributes to the regulation of gene expression. The nuclear space is compartmentalized in several domains such as the nucleolus, chromocentres, telomeres, protein bodies, and the nuclear periphery without the presence of a membrane around these domains. The role of these domains and their possible impact on nuclear activities is currently under intense investigation. In this review, we discuss new data from research in plants that clarify functional links between the organization of different nuclear domains and plant genome function with an emphasis on the potential of this organization for gene regulation.
Keywords: telomeres; nucleolus; Chromatin; Cell Nucleolus; Cell Nucleus; topologically associated domains (TADs); nuclear domains; liquid–liquid phase separation (LLPS); rostliny; buněčné jádro; nuclear periphery; regulace genové exprese; 3D Chromatin organization; chromatin; Plants; chromocentres; Gene Expression Regulation; buněčné jadérko; nuclear bodies; gene expression